Co-designing choice: objectivity, aesthetics and agency in audio-description. (4th March 2021) - Hadley, Bree; Rieger, Janice
ABSTRACT: Even though museums and galleries have made efforts to become more inclusive, many continue to find it challenging to engage visitors who are blind or have low vision. The 'Vis-ability' exhibition, presented at the QUT Art Museum in 2019 was an exhibition curated with clear social inclusion goals from the outset. Through it, the museum sought to develop innovative, cost effective, and readily replicable techniques to allow blind and low vision visitors and artists to engage with the institution and its collections. The results affirm the benefits of offering blind and low vision visitors a spectrum of engagement choices, and also affirm that blind and low vision artists and visitors have capacity to make a critical contribution in co-designing that spectrum of choices. This exhibition and its use of multisensorial elements offers a useful prompt to museums to engage this community more fully in co-designing inclusion in the future.